(untitled) (Metallurgy and Foundry Engineering, 2006)
Mathematical model of high-efficiency ceramic recuperators using the new generation of shapes was elaborated. The parameters and characteristics magnesia, fusion cast alumina-mullite-zirconia, chamotte recuperator shapes were compared. Ceramic recuperator to glass tank was calculated by the model.